Suggestopedia in Arabic Language Learning (A Case Study of Reading Skills Instruction for Seventh-Grade Students at MTs N 4 Jember) - Siti Nurfadhilah; Sa’idatul Abidah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
There are four language skills, such as listening, reading, speaking, and writing. These skills are from the goal of universal Arabic education that must be learned, so that all students can master it. Reading skills require serious attention because reading skills cannot be obtained automatically, but must be studied and practiced. However, there are many aspects that cause difficulties for students in the learning process. One of the reasons is that there are various kinds of student personalities in the classroom that make teachers must be smart in choosing methods. One of the appropriate strategies as an effort to handle the case is to use the